Recombinant vaccinia vector-based vaccine (Tiantan) boosting a novel HBV subunit vaccine induced more robust and lasting immunity in rhesus macaques. Issue 25 (5th June 2017) - Deng, Yao; Chuai, Xia; Chen, Pan; Chen, Hong; Wang, Wen; Ruan, Li; Li, Wenhui; Tan, Wenjie
Highlights: We explored several prime-boost strategies of HBV vaccines in rhesus macaques. A longitudinal immunity study was investigated until 79 weeks post-vaccination. HBSS1/RVJSS1/RVJSS1 induced more robust and lasting CMI in macaques. This vaccination regimen show promise as therapeutic applications for humans. Abstract: This study explored several prime-boost strategies in rhesus macaques using various novel hepatitis B virus (HBV) vaccines that showed promise as prophylactic and therapeutic approaches in our previous study using in a mouse model. The tested vaccines included an HBV particle subunit (HBSS1) vaccine and the recombinant vaccinia (RVJSS1) or adenoviral (rAdSS1) vector-based vaccines containing S (1–223 aa) and PreS1 (21–47 aa). The strength and maintenance of humoral activity (IgG and neutralizing antibodies) and cellular immunity (interferon-γ production assessed by IFN-γ enzyme-linked immunosorbent spot (ELISpot) assay) were investigated in a longitudinal study following various vaccination protocols until 79 weeks post-vaccination. We found that HBSS1/RVJSS1 heterologous prime-boost elicits similar strong humoral immunity but more robust and lasting cellular immunity (CMI) than HBSS1/HBSS1 homologous vaccination in rhesus macaques. Furthermore, HBSS1/RVJSS1/RVJSS1 induced more robust and lasting CMI in macaques than did HBSS1/HBSS1/rAdSS1 vaccination. Therefore, HBSS1/RVJSS1/RVJSS1 is most promising candidates for protecting humans against HBV infection, especially for therapeutic application.